The castle of Llyr - Alexander, Lloyd (New York, New York Bantam Doubleday Dell Books for Young Readers, 1990)
When Princess Eilonwy is sent to the Isle of Mona for training, she is bewitched by the evil enchantress Achren, so Taran and other friends must try to rescue her.
"A yearling book."
Keywords: Fantasy; Fairy tales